Perancangan Desain Karakter Wisatawan dalam Buku Ilustrasi Wisata Trenggalek untuk Usia 18-25 Tahun - Faliq Firashan; Aninditya Daniar; Alfian Candra Ayuswantana (Lembaga Pengembangan Kinerja Dosen, 2026)
Trenggalek Regency is one of the regencies located in the southern part of East Java that has high potential for natural tourism, such as caves, waterfalls, and beaches. However, this potential is not yet widely known by people from outside the region, especially the younger generation. The low level of awareness among people outside the region is influenced by limited access to information about Trenggalek’s tourism. Therefore, an effective medium that can attract the attention of young people is needed, such as an illustrated book. Based on the questionnaire results, the majority of respondents show a high interest in illustrated books. In an illustrated book, an engaging character is needed to convey messages so that readers do not feel bored. The method used in this study is a mixed-method approach with a descriptive analyze. This approach is applied to analyze data obtained from observations, interviews, literature studies, and questionnaires, as well as to develop design concepts and outcomes. This research aims to increase awareness and knowledge of people outside Trenggalek about Trenggalek’s tourism. By highlighting the topic of character design in the illustrated tourism book of Trenggalek, it is expected that readers can easily absorb and understand the content of the book.